Sistem Informasi Geografis Kesesuaian Lahan Perumahan di Kota Malang menggunakan Metode MCE - Muhammad Hadi Selamet Hariyanto; Fatwa Ramdani; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
This research is applying Multi-Criteria Evaluation (MCE) method to analyze the land suitability of residential in Malang. Criteria such as safety, convenience, and compatibility are used in this research based on Indonesia National Standard procedure of housing environment planning in urban area. There are two MCE techniques that are used; those are WLC and OWA techniques. Both techniques are giving different results, and the closest result to the reality is the OWA technique. Then the results of both techniques are validated using ROC analysis method. The percentage of the OWA model is showing 79%, while WLC model is only showing 67%. Then, WLC and OWA models are incorporated into geographic information systems that have been tested using Black-box and White-box methods in order to make the Malang's society can access it